E-Commerce Website System Security Improvement Strategy Using AHP and FAHP Methods - Dhiya' Ulhaq Ahmad Ramsi; Moh. Azzam Priyanto; Farras Hafizh Zidane; Mochammad Yusuf Pratama; Eristya Maya Safitri (International Journal of Computer, Network Security and Information System, 2023)
Security of e-commerce websites becomes one ofthe factors to develop e-commerce services. A secure e-commercewebsite can protect the personal information and transactionaldata of the user. However, in its everyday use, there is someproblem that appears related to security. The purpose of thiswriting is to establish a security strategy for an e-commercewebsite based on the result of AHP and FAHP measuring. Theresearch method used in this writing is Analytic HierarchyProcess (AHP) and Fuzzy Analytic Hierarchy Process (FAHP) totake a decision. AHP is used as a tool to analyze decision-makingthat comes close to a real-life situation and is used a lot in variousfields, like evaluation, assessment, forecasting, and others.Meanwhile, fuzzy logic is used for a vague variable. The results ofthe research that has been done are that several e-commercewebsites get low scores on system security measurements usingthe AHP and FAHP measurement methods. Therefore a strategyis needed to increase the security of the e-commerce websitesystem so that users' personal information can be properlymaintained. Keywords—E-Commerce; AHP; FAHP; Security